Transport of critically sick children to transplant centres - Romit Saxena; Maninder Dhaliwal; Padmanabhan Ramnarayan; Akash Deep (Journal of Pediatric Critical Care, 2018)
Transport of a critically sick child can be a very challenging task. This requires close coordination between transport team, referring and receiving centers. In this review, we emphasize on children who are transported for transplant consideration to higher centers specifically liver, renal and bone marrow transplant recipients. It is an attempt to reinforce the importance of effective communication, regular and structured training, checklists and handover. We also state a few common scenarios that may arise during transportation of such critically sick patients.